(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Thuy NP, Nam NN, Trai NN, Thao NHX, Phong VT, Khang DT. 2022. Potential of Trichoderma spp. isolated in the rhizosphere to produce biofertilizer from organic materials. Biodiversitas 23: 6386-6396. Trichoderma spp. are filamentous fungi present in nearly all soils and capable of secreting large amounts of cellulase enzymes that can degrade carbohydrate polymer. In the current study, eight isolates of Trichoderma spp. (TC10-RL11, CT11-VO11, CN2-DP11, CN1-DP11, TC9-RL11, CN4-VR11, CK6-VC11, and TC8-RL11) were isolated. Among the eight fungal strains, the CN4-VR11 had highly potent CMC degradation with a halo’s diameter zone of 8.7 ± 1.5 cm. The BLAST result indicates that the CN4-VR11 strains and Trichoderma reesei had a similarity of 98.92% with a max score of 1158 and an E-value of 0.0. The Trichoderma reesei CN4-VR11 was selected for bioproduct production. The application of Trichoderma reesei CN4-VR11 bioproduct passively increased the efficient decomposition of the organic fertilizers, after only 30 days of incubation, the total organic matter content ? 20% was observed to be soft, spongy, and brown-back in color. According to the Government of Vietnam’s Decree No. 108/2017/ND-CP on fertilizer management, dated September 20, 2017, the T5 and T7 treatments were chosen for the production of granular bio-compost, which has a more practical use in agricultural land.